Akame ga kill! 11 - Takahiro, 1981- (Yen Press, 2017)
"Syura's secret police capture Tatsumi and Lubbock during their reconnaissance mission! Tatsumi comes face-to-face with General Esdeath once more, but will they join forces? And what awaits Tatsumi should he refuse? Love and death intertwine!"--